Addition for the lowest connection in grammatical guidance (Damascus University Journal of arts and humanities sciences, 2025)
This is a type of addition is based on the existence of the minimum confusion among additioners. Its chapter is the expansion as an example of figurative  language other than literal meaning.Syntax books referred to it using poetic explanations and interpretations and so forth. It was a mensurable proof upon which they built their opinion on instructions since it was published (said) by Arabs and was one of their habits.Abu Ali al-Farisi identified the condition of approving this addition. Al-Marzwki mentioned the places of meaning approximations and expansions.Al- Zamakhshari expanded on its uses in his instructions. His fellows cited it by reporting, disagreeing and adding. One of its most common forms is approximating its meaning as in “fii”.The outcomes of the research indicates that addition is one of the various depths of the Arabic language and a ded from the crafts of its eloquence that led to fathoming its meaning and drawing attention to it.
Keywords: addition; the lowest connection; extension; Metaphor